Mineralogía de las arcillas calcinadas de la base de la Fm. Escucha en el área de Foz-Calanda. - Fernández Turiel, J.L.; Alastuey, A.; Bastida Cuairán, J.; Querol, X.; Signes, M. (Cuadernos de Geología Ibérica, 1993)
Sin resumen